2002
DOI: 10.1161/01.hyp.0000022570.02119.75
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride, a Specific Drug for Hypertension in Black People With T594M Variant?

Abstract: Abstract-The T594M polymorphism of the epithelial sodium channel is found in Ϸ5% of people of African origin and is significantly associated with high blood pressure. Although the T594M polymorphism could increase renal sodium absorption through affected channels, it is not known whether this polymorphism causes hypertension. Amiloride specifically inhibits overactive sodium channels and effectively controls blood pressure in Liddle's syndrome, in which hypertension is caused by separate epithelial sodium chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 14 publications
2
52
0
1
Order By: Relevance
“…Therefore, our data call into question the notion advanced by a previous study in which amiloride monotherapy appeared to have a particularly dramatic BP-lowering effect in black hypertensives with the T594M allele. 8 The confirmation of the null hypothesis in our study may be related to several important methodological factors, including: (1) measurement of BP with ambulatory monitoring rather than office measurements; (2) a lower average level of pretreatment BP in our study, which avoids exaggeration of BP response; and, most importantly, (3) inclusion of a control group of black participants lacking the T594M allele. It is possible that a small gene effect was obscured by the number of T594M-positive subjects studied, and we did not assess response to dynamic challenges, such as a high-salt diet.…”
Section: Pharmacogenetic Studysupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, our data call into question the notion advanced by a previous study in which amiloride monotherapy appeared to have a particularly dramatic BP-lowering effect in black hypertensives with the T594M allele. 8 The confirmation of the null hypothesis in our study may be related to several important methodological factors, including: (1) measurement of BP with ambulatory monitoring rather than office measurements; (2) a lower average level of pretreatment BP in our study, which avoids exaggeration of BP response; and, most importantly, (3) inclusion of a control group of black participants lacking the T594M allele. It is possible that a small gene effect was obscured by the number of T594M-positive subjects studied, and we did not assess response to dynamic challenges, such as a high-salt diet.…”
Section: Pharmacogenetic Studysupporting
confidence: 50%
“…3 In a study of 14 T594M heterozygotes with mild-to-moderate hypertension, amiloride monotherapy was as effective in controlling BP as usual empiric combination therapy with 2 or 3 standard antihypertensive agents. 8 However, the conclusions from that study must be considered preliminary, because no control group of black hypertensives lacking the T594M allele was studied for comparison.…”
mentioning
confidence: 99%
“…These functional analyses may explain the clinical phenotype of patients with the T594M mutation. The T594M mutation contributes to the elevation of blood pressure and suggests that consideration should be given to the use of amiloride in affected individuals (19).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation has been reported to be the common in black people with essential hypertension in some studies (18,19), but not another (20). Some studies have reported that this mutation is common among black individuals with essential hypertension (18,19), but another study found no such association (20).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation